Análisis jurídico en base a casos de recuperación por retención indebida del menor incumpliendo el Principio de Celeridad. - Villarreal Pérez, Paola Viviana (2024)
In a constitutional state of rights, including Ecuador, such attention is recognized to priority attention groups, especially children as subjects of rights. However, the processes of recovery of minors due to undue retention show a lack of speed, generating distrust, insecurity and concern between citizens, among the procedural parties and even in the administration of justice itself. In the timeline, critical knots have been identified in its processing, until reaching its recovery, which in many cases, despite the existence of a legal sanctioning provision from the competent authority, have not been able to be executed either. Therefore, this work aims to legally analyze the cases of protection measures that must be applied when there is a recovery due to undue retention of a minor in violation of the principle of speed. Multiple procedural omissions and the excessive time that these judicial files generate have been evidenced, considering that in the Organic Code of Children and Adolescents and in the investigations carried out in different sources, the necessary and urgent attention is not given to these cases, making it necessary to legally analyze the violation of the principle of speed both in the national and international context in judicial procedures for the recovery of a minor due to undue detention. This research is documentary, the modality that was applied was qualitative and the methods used were inductive, deductive, analytical, synthetic, and historical-logical to draw conclusions about the problems generated in these processes through a critical legal analysis.